Isolation and Culture of Cereal Protoplasts Part 2: Embryogenesis and Plantlet Formation from Protoplasts of Pennisetum americanum - Vasil, V.; Vasil, I.K.
Protoplasts isolated from embryogenic suspension cultures derived from immature embryos of pearl millet (Pennisetum americanum)gave rise to cell masses. These cell masses upon transfer to a hormone-free medium formed embryoids, which further developed into planflets with roots and shoots.
Keywords: PEARL MILLET; PENNISETUM AMERICANUM; CEREALS; PROTOPLASTS; EMBRYOGENESIS; PLANT REGENERATION